Integrated Marketing Strategy to Counter Low-Priced Brands in Indonesia’s Oversupplied Retail Cement Market: SIG Case - Media, Sasha; Setiawan, Iwan (Syntax Literate, 2025)
In Indonesia’s oversupplied retail cement market, SIG faces intense competition from low-priced brands, leading to profit decline and premium brand dilution. Although SIG’s multi-brand strategy shows some success, it underutilized due to challenges in Product & Pricing, Sales & Distribution, and Brand & Marketing Communication aspects. This research develops an integrated strategy framework to protect premium brand equity and secure market share aspiring for sustainable growth. Combining primary interviews with secondary internal and market data, the study applies Porter’s Five Forces, Marketing Mix, Brand Equity, Customer Path, and TOWS matrix to integrate internal and external perspectives. Findings reveal SIG’s unmatched distribution scale but slower pricing responsiveness and unclear brand roles. Customers perceive brands as interchangeable, while retail partners face channel conflicts. The study recommends a data-driven, adaptive integrated marketing strategy emphasizing pricing and brand reposition governance, retail segmentation, harmonized incentives and distribution scheme, real-time monitoring, differentiated and targeted brand activation, and contractor-retailer ecosystem building.